Religious Moderation Based on Local Wisdom: (Semiotika Analysis of Roland Barthes in the Novel Hati Suhita by Khilma Anis) - Puji Laksono (Prodi Sosiologi Agama, 2024)
Religious moderation is a perspective, behavior and attitude that always chooses a position in the middle, is always based on justice, and does not take an extreme position in religious practice. four indicators of religious moderation, namely tolerance, national commitment, non-violence, and acceptance of tradition. In the final indicator, namely acceptance of tradition can be the key to building a paradigm and attitude of religious moderation with a local cultural approach. Religious moderation based on local wisdom is interesting to study. For this reason, researchers analyzed a novel entitled